Saturday

August 23, 2014

August 23, 2014

Posted by **Ramesh Reddy** on Sunday, September 4, 2011 at 12:15pm.

I tried to solve the above problem like this:

(6√x-11)(√x+6)=(3√x)(2√x+1)

6√x(√x+6)-11(√x+6)=(3√x)(2√x)+(3√x)(1)

6x+36√x-11√x-66=6x+3√x

36√x-11√x-66=3√x

36√x=3√x+11√x+66

36√x=14√x+66

36√x-14√x=66

22√x=66

2√x=6

√x=6/2

√x=3

x=(3)2

x=9.

- maths -
**bobpursley**, Sunday, September 4, 2011 at 1:01pmcheck your answer: sqrt 9 is 3

6*3-11)(3+6)=(9)(7)

7*9=9*7

correct

**Related Questions**

Math - Find an equation of the line that bisects the obtuse angles formed by the...

Algebra - How would i complete these problems? 1. (√6mn)^5 2. ^3√16x...

Algebra Work Check - 1. 5√6 * 1/6√216 5/6 * √1296 5/6 * √...

Algebra - Simplify the expressions and solve the equations 1. 2√3 - √...

algebra 1 - alright i have a few questions if its ok..? Simplify: 1. -2√(...

Precalculus - Determine the exact value of cos 465 degrees a) √3 + √...

Math - Determine the exact value of cos 465 degrees a) √3 + √2/2 b...

Math help Ms. Sue please - 1. What is the simplified form of the expression? 7m^...

grade 11 math - I don't get how to do this. I'm so lost please help me. ...

algebra 1 help - simplifying square roots 1) find volume of this prism? v=bwh b...